Memristors and Memristive Systems - Tetzlaff, Ronald (Springer New York : Imprint: Springer, 2014)
This book provides a comprehensive overview of current research on memristors, memcapacitors and, meminductors. In addition to an historical overview of the research in this area, coverage includes the theory behind memristive circuits, as well as memcapacitance, and meminductance.  Details are shown for recent applications of memristors for resistive random access memories, neuromorphic systems and hybrid CMOS/memristor circuits. Methods for the simulation of memristors are demonstrated and an introduction to neuromorphic modeling is provided. ·         Provides a single-source reference to the state of the art in memristor research; ·         Explains the theory of memristors and memristive networks; ·         Demonstrates a variety of memristor realizations with focus on resistive random access memories; ·         Enables readers to use neuromorphic modeling to understand complex phenomena in biological systems.